Modelling and Validation of 3D FEM for Laterally Loaded Single Pile - Wong, Soon Yee; Kok, Sien Ti; Choong, Wee Kang; Mohamed, Abdullahi Ali (International Journal of Integrated Engineering, 2018)
At present, researchers are increasingly in favour of Three-Dimensional Finite Element Method (3D FEM) during design process to better understand ground mechanisms and soil-structure interactions. Subsequently, it is essentially a back-analysis modelling procedure for applications in design and post-construction or failure investigation. This research aims to use 3D FEM to validate laterally loaded single pile response. Two different case studies are selected, Firstly, a published case study comparing the p-y method and finite element method for the behaviour of single pile subjected to the horizontal forces is investigated. The second case is one of published centrifuge data and finite element method for the behaviour of pile behind retaining wall subjected to excavation-induced soil movement. Through comparison with the results from case studies, 3D FEM is in good agreement with the general trend observed in field or centrifuge measurements and gives better validation or prediction of lateral deflection characteristics compared to other conventional methods.